TEACHING ENGLISH WITH STORY TELLING METHOD IN EARLY CHILDHOOD EDUCATION TEACHERS - Amalia, Arsyi Rizqia (University of Muhammadiyah Malang, 2018)
The importance of English has an impact on the needs of future generations to learn English from an early age especially in Early Childhood Education and vocabulary is an important component that can support the mastery of all four language skills. Facing the difficulty of learning vocabulary, a method that is appropriate for the age of child development is needed. One of methods that could be used is story telling. The research method used in this research is qualitative descriptive. The sample in this study was six early childhood education teachers in Sukabumi. Data collecting techniques were presentations and questionnaires. The presentations were held twice, in front of peers of early childhood education teachers and in front of students of early childhood education. After presentation, the questionnaires were conducted related to the implementation of the story telling method to the teacher. Based on the data collected, Teaching English withÂ Story Telling Method give a good response with indicators shows thatÂ the content of the story, the properties used, the variety of vocabulary taught, moral values based on the stories and the ability of delivering the English vocabulary were good and suitable with the age of early childhood education.